The Ri-elaboration of the Collective Sphere. New Paths of Sociality and Groups-Formation among the New Generations - Pirni, Andrea; Raffini, Luca (PARTECIPAZIONE E CONFLITTO, 2017)
Goal of the article is to contribute to the understanding of the reinvention of politics in young generations moving from an in depth sociological examination of the change occurring in the structure of society and in its self-definition. The objective is to grasp the ambiguity and the ambivalence characterizing the ongoing scenery of change. To carry out this analysis, we will refer to Simmel’s seminar theory of society as a network of relations and, along this line, to the contributions of authors such as Beck, Giddens, Touraine, Melucci, Castells, on the development of the late modernity and the network society. The hy-pothesis we follow is that the younger generations present multiple and original synthesis between sub-jectivity and the collective dimension. The emergence of reticular and fluid relations among individuals fosters the process of individualization and the same reinvention of the nature of social ties. We frame the qualitative transformation of the concept of "group" and "collective" as the culmination of a process of individuation, which does not entail a disappearance of intermediate groups, but that multiplies and radically alters their structure. Groups are more and more fluid and their borders porous. Individuals are no longer defined by their belonging to groups, as the same belonging to groups becomes a contingent and a negotiated act